How do the unemployed search for a job? Evidence from the EU Labour Force Survey - Ronald Bachmann; Daniel Baumgarten (IZA Journal of European Labor Studies, 2013)
Using harmonised micro data, this paper investigates the job search behaviour of the unemployed in Europe. The analysis focuses on the importance of individual and household characteristics in this context, as well as on cross-country differences in Europe. Our findings suggest that both individual and household characteristics play an important role, with the latter being more decisive for women. However, even when controlling for these factors, remarkable differences remain between countries, which are associated with institutional characteristics at the country level.
Keywords: J20; J64; C38; 330; Job search; Search channels